THE INFLUENCE OF SOCIAL MEDIA ON MENTAL HEALTH AMONG YOUNG PEOPLE - Radjabova Shokhista Shukurulloyevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Social media has become an essential part of modern life, especially for young people. While it offers opportunities for communication and self-expression, it also raises serious concerns about mental health. This article analyzes the impact of social media on psychological well-being and discusses strategies to reduce its negative effects.